Determinants of ectopic pregnancy among pregnant women attending referral hospitals in southwestern part of Oromia regional state, Southwest Ethiopia: a multi-center case control study - Urge Gerema; Tilahun Alemayehu; Getachew Chane; Diliab Desta; Amenu Diriba (BMC, 2021)
Abstract Background Ectopic pregnancy is an abnormal condition in which implantation of the blastocyst occurs outside the endometrium of the uterus. It is gynecological important, particularly in the developing world, because of associated with enormous rate of high morbidity, during the first trimester of pregnancy. A better understanding of its risk factors can help to prevent its prevalence. However, the determinants of ectopic pregnancy are not well understood and few researches conducted in our country were based on secondary data covering small scale area. This study aimed to identify determinants of ectopic pregnancy among pregnant women attending referral hospitals in Southwestern part of Oromia regional state, Southwest Ethiopia. Methods Hospital-based case control study was employed from June 1 to September 30, 2019. The study was conducted in five referral hospitals in Southwestern part of Oromia regional state. Final sample size includes 59 cases and 118 controls. Data were entered by using Epidata version 3.1 and analyzed using SPSS version 23. Descriptive statistics were used to explore the data. All explanatory variables with p-value of < 0.25 in bi-variable analysis, then entered into multivariable logistic regression. Associated factors were identified at 95% confidence interval (p < 0.05). Results Out of 177 (59 cases and 118 controls) participants, 174 (58 cases and 116 controls) were participating in the study. Prior two or more induced abortions [AOR = 3.95:95% CI: 1.22-13.05], previous history of caesarean section [AOR = 3.4:95% CI: 1.11-10.94], marital status (being single) [AOR = 4.04:95%CI: 1.23-13.21], reporting prior recurrent sexual transmitted infection [AOR = 2.25:95%CI: 1.00-5.51], prior history of tubal surgery [AOR = 3.32:95%CI: 1.09-10.13], were more likely to have an ectopic pregnancy with their respective AOR with 95%CI. Conclusion It was found that having a history of more than two induced abortions during previous pregnancies, marital status (single), recurrent sexual transmitted infection, prior history of tubal surgery and experiencing prior caesarean section were found to be determinants of ectopic pregnancy. Hospitals should give emphasis on prevention and early detection of risks of ectopic pregnancy and create awareness in order to reduce the burden of ectopic pregnancy.